Research Trends On Local Wisdom In Indonesia: A Bibliometric Analysis (2015-2024) - Sapriya, Sapriya; Supriatna, Mamat; Somantri, Mubarok; Lugina, Tiana Dara; Saefudin, Asep; Maftuh, Bunyamin (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study maps the development of local wisdom research in Indonesia using a bibliometric approach to identify publication trends, dominant themes, emerging topics, and research gaps. Data were retrieved from Google Scholar on 13 May 2024, covering publications from 2015 to 2024. After screening and deduplication, 545 validated documents were analyzed using Publish or Perish, Mendeley, and VOSviewer through citation analysis, keyword co-occurrence, network visualization, overlay visualization, and density mapping. The results show a substantial increase in publication output, particularly after 2022, indicating growing scholarly attention to local wisdom in relation to education, culture, and sustainable development. The dominant thematic clusters are centered on character education, curriculum integration, student learning, and value transmission demonstrating that local wisdom has primarily been positioned as pedagogical within indonesian scholarship. Overlay analysis reveals a shift from preservation-oriented studies toward implementation-based themes such as innovation, strategy, and contextual learning. However, weak keyword connectivity is found in areas related to student engagement, participatory learning, experiential approaches, digital preservation, and interdisciplinary collaboration, indicating underexplored directions in the current literature. The findings further suggest that local wisdom research in Indonesia is more education-oriented than ecological or governance-oriented, differing from several international trends in indigenous knowledge studies. Future research should therefore prioritize student-centered learning models, technology-supported cultural preservation, and stronger collaboration between educational institutions and local communities.